2008
DOI: 10.1088/0953-2048/21/9/095015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of MgB2films grown at various temperatures by hybrid physical–chemical vapour deposition

Abstract: A Hybrid Physical-Chemical Vapour Deposition (HPCVD) system consisting of separately controlled Mg-source heater and substrate heater is used to grow MgB 2 thin films and thick films at various temperatures. We are able to grow superconducting MgB 2 thin films at temperatures as low as 350°C with a T c0 of 35.5 K. MgB 2 films up to 4 m in thickness grown at 550°C have J c over 10 6 A/cm 2 at 5 K and zero applied field. The low deposition temperature of MgB 2 films is desirable for all-MgB 2 tunnel junctions a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Within the temperature range from 600 to 720 • C, a substantial decrease, by a factor of more than 2, in the deposition rate with increasing substrate temperature is observed for both 40 and 80 Torr total pressures. Using an HPCVD setup with separate Mg and substrate heaters, Chen et al have found the same general behavior in an even broader temperature range [17]. We do not completely understand this strong reduction of deposition rate at high temperatures, but it may be related to the premature decomposition of B 2 H 6 at high temperatures, which reduces the B supply to the growth process [18].…”
Section: Deposition Rate Of Mgb 2 Film By Hpcvdmentioning
confidence: 75%
“…Within the temperature range from 600 to 720 • C, a substantial decrease, by a factor of more than 2, in the deposition rate with increasing substrate temperature is observed for both 40 and 80 Torr total pressures. Using an HPCVD setup with separate Mg and substrate heaters, Chen et al have found the same general behavior in an even broader temperature range [17]. We do not completely understand this strong reduction of deposition rate at high temperatures, but it may be related to the premature decomposition of B 2 H 6 at high temperatures, which reduces the B supply to the growth process [18].…”
Section: Deposition Rate Of Mgb 2 Film By Hpcvdmentioning
confidence: 75%
“…In the original HPCVD system the Mg partial pressure is linked to the substrate temperature, limiting the substrate temperature to around 700 • C. In order to broaden the parameter space for the deposition of MgB 2 films, it is necessary to control the temperature of the Mg source, and thus the Mg vapor pressure, independently from the substrate temperature. Two modified HPCVD configurations with separate Mg source and substrate heaters have been reported: one with an impinging-jet diborane supply capable of depositing MgB 2 films at very high rate (2 μm min −1 ) [57], and the other demonstrating the deposition of superconducting MgB 2 films from 350 to 750 • C [58]. Figure 5 shows the resistivity versus temperature curves for MgB 2 films grown at different temperatures.…”
Section: Hybrid Physical-chemical Vapor Depositionmentioning
confidence: 99%
“…Experimental syntheses of MgB 2 by vapour [57] or solid state [31,58] methods are well documented in the literature and, in comparison to syntheses of many other superconductors, are uncomplicated. Commercial production of MgB 2 wires [59,60] was achieved soon after the publication by Nagamatsu et al [21].…”
Section: Mgb 2 : Low-frequency Raman Peaksmentioning
confidence: 99%